MANAJEMEN PERSONALIA DI LEMBAGA PENDIDIKAN - Nuraini (JURNAL ILMIAH EDUKATIF, 2022)
Personnel management is an effort to obtain the right type and number of personnel needed to complete the goals of the organization. Planning personnel, knowledge that has the aim of finding and submitting job applications by providing a motivation so that they can know the knowledge and abilities, staffing in an educational institution. This personnel planning consists of: outreach of education personnel and orientation and placement of educational personnel. Personnel development activities consist of: procedures or reviews to ensure efforts to utilize, improve and increase work productivity. Assessment and promotion consists of assessment of educational staff, transfer, promotion, and demotion, as well as compensation and dismissal of education personnel.